Phenotypes of Women with and Without Endometriosis and Relationship with Functional Pain Disability. Issue 7 (1st December 2020) - Evans, Subhadra; Mikocka-Walus, Antonina; Olive, Lisa; Seidman, Laura C; Druitt, Marilla; Payne, Laura A
Abstract: Objective: Primary dysmenorrhea and secondary dysmenorrhea due to endometriosis share overlapping symptoms and likely demonstrate aspects of central sensitization. The present study aimed to identify distinct phenotypes of women who have dysmenorrhea with and without endometriosis to shed light on the unique mechanisms contributing to the pathogenesis of each condition. Methods: An online survey was used to investigate the relationship between ratings of menstrual pain severity, menstrual symptoms (abdominal cramps, abdominal discomfort, low back pain, headache, body aches, bloating, nausea, diarrhea, increased bowel movements), widespread pain, and functional pain disability in a community sample of 1, 354 women (aged 18–50) with menstrual pain in Australia. Results: Compared with women without endometriosis, those with endometriosis had statistically significant higher menstrual pain severity ( P <0.01), symptom severity and fatigue (all symptoms P <0.001, although only cramps and bloating were clinically significant), widespread pain sites ( P <0.001), and functional pain disability ( P <0.001, although this difference was not clinically significant). When examining symptoms by pain severity, women with severe menstrual pain were more likely to experience symptoms than women with less severe pain, regardless of the presence of endometriosis. Similar predictors of functional pain disability emerged for women with and without endometriosis, such as body aches, nausea, fatigue, and widespread pain, respectively, suggesting the presence of central sensitization in both groups. Logistic regression revealed that after accounting for menstrual pain severity (odds ratio [OR], 1.61) and duration (OR, 1.04), symptoms of bloating (OR, 1.12), nausea (OR, 1.07), and widespread pain sites (OR, 1.06) significantly predicted the presence of endometriosis. Conclusions: The findings suggest that phenotypes specific to endometriosis can be identified.